A dictionary of earth sciences - Allaby, Michael (Oxford University Press, 2008)
Covers topics such as climatology, economic geology, geochemistry, oceanography, palaeontology, petrology, and volcanology. Includes entries on planetary science, remote sensing, statistics, and sequence stratigraphy, wind strength scales, material, temporal, and chronostratigraphic units, geologic, lunar, and Martian time scales.
Previous ed. published as: The concise Oxford dictionary of earth sciences. 1990.
Keywords: Earth sciences -- Dictionaries.; Englisch.; elektronické knihy; electronic books